ADAMTS4-specific MR probe to assess aortic aneurysms in vivo using synthetic peptide libraries - Kaufmann, Jan O.; Brangsch, Julia; Kader, Avan; Saatz, Jessica; Mangarova, Dilyana B.; Zacharias, Martin; Kempf, Wolfgang E.; Schwaar, Timm; Ponader, Marco; Adams, Lisa C.; Moeckel, Jana; Botnar, Rene M.; et al. (Nature Communications, 2022)
The incidence of abdominal aortic aneurysms (AAAs) has substantially increased during the last 20 years and their rupture remains the third most common cause of sudden death in the cardiovascular field after myocardial infarction and stroke. The only established clinical parameter to assess AAAs is based on the aneurysm size. Novel biomarkers are needed to improve the assessment of the risk of rupture. ADAMTS4 (A Disintegrin And Metalloproteinase with ThromboSpondin motifs 4) is a strongly upregulated proteoglycan cleaving enzyme in the unstable course of AAAs. In the screening of a one-bead-one-compound library against ADAMTS4, a low-molecular-weight cyclic peptide is discovered with favorable properties for in vivo molecular magnetic resonance imaging applications. After identification and characterization, it’s potential is evaluated in an AAA mouse model. The ADAMTS4-specific probe enables the in vivo imaging-based prediction of aneurysm expansion and rupture.
CRIS-Team Scopus Importer:2023-03-08